Resistindo, conciliando e vivendo: o quotidiano dos moradores da periferia de Fortaleza - Oliveira, João Lúcio Farias de (1997)
Understand the daily life of residents in the outskirts of Fortaleza by reference to the popular organizations is the central theme of the research. The study sought to understand the lived world of the residents of the periphery focusing on the content of their actions, relations of solidarity and identity construction from the reference groups and interaction existing in the neighborhood, without losing sight of the forms of domination and historical inequalities hairs residents lived in the periphery. This process could be understood from the fact Set San Miguel neighborhood on the outskirts of town. Optionally two methodological aspects have greater visibility in work, the forms of resistance and the living spaces where the playful spirit is more pronounced, these aspects are interrelated to other elements of the socio-cultural dynamics and politics existing in the neighborhood searched